The epidemiology of physical disability Among elderly in Kota Bharu, Kelantan - Dahalan, Latifah (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
Objective : In Malaysia, the decline in fertility and mortality as well as improvement in life expectancy were said to be responsible for the aging of the population by the year 2020. Our life expectancy at birth has increased from 56 years in the 1950s to 70.4 years for males and 75.3 years for females in the year 2002. The purpose of this study is to present a broad overview of current knowledge of socio-demographic characteristics and health conditions among elderly population age 60 and over. Methods :This is a cross-sectional study which involved a total of 270 participants of elderly, aged 60 years and above under 3 health clinics of Kota Bharu operational areas. Guided- questionnaire were administered by the researcher and the subjects were asked to Results: Sixty-six percent of elderly were women and majority of them were muslim ( go to clinics or community centre on the appointed date for physical examination and 98.5%). Nearly 62% of them never have any formal education and about 62% were blood taking for fasting blood sugar and total cholesterol. unemployed. Regarding the income, more than 50% dependent on their child and about 66% of them have income less than RM 200. The prevalence of elderly who smoked, physically active, and overweight/obese were 17%, 39.6% and 30.8 respectively. Elderlywho have visual impairment were 63.3°/o and 37% have hearing impairment. About 15% have fasting blood sugar more than 7.8 mmol/1, 68.8% have total cholesterol level more than 5.2 mmol/1, 47o/o have diastolic hypertension, and 57.4% have systolic hypertension. When using activities of daily living ( ADLs) as an indicator for physical disabilities, the prevalence of physical disabilities was I 0. 7%, whereas 34.8% for instrumental activities of daily living (IADLs). Conclusion: Older population is varied in personal background, lifestyle behavior, medical conditions and physical disabilities. This diversity should be acknowledged in social policy as well as government on the prevention of chronic diseases which are either preventable or modifiable with healthy lifestyle habits as well as with some correction measures.